Due To The Legal Non-Compliance of State Administrative Officers With The Implementation of Forced Money (Dwangsom) In The Execution of State Administrative Decisions - Pattipawae, Dezonda Rosiana; Abdullah, Abdullah; Salmon, Hendrik; Lainsamputty, Natanel (SASI, 2022)
Introduction: The non-compliance of the state administrative body or official with the TUN Court decision can be in the form of not revoking the disputed State Administrative decision, not revoking the TUN decision, not issuing a TUN decision, not complying with the obligation to pay compensation set by the court and not complying to rehabilitate the good name plaintiff.Purposes of the Research: The purpose of this study is to examine and analyze the payment of forced money and administrative sanctions against state administration officials who do not comply with the state administration's decisions and legal actions due to non-compliance of state administration officials to the application of forced money (dwangson) in the execution of state administration decisions.Methods of the Research: The writing method used is sociological juridical research. The location of this research is the Ambon State Administrative Court, the Ambon City Government Legal Division, the Maluku Province Law and Human Rights Bureau and the Central Maluku District Government Law Department.Results of the Research: The results of the study indicate that the disobedience of State Administrative Officials in implementing decisions that already have permanent legal force because there are no regulations and or legal provisions regarding forced payment of money to be implemented if the State Administrative Officials do not implement decisions that already have permanent legal force, and there is no special agency or executive body